PWE-208 How common is pancreatic exocrine insufficiency in primary care?. (22nd June 2015) - Campbell, JA; Francis, KA; Kurien, M; Hopper, AD; Joy, D; Lee, S; Ramadas, A; Taha, H; Sanders, DS
Abstract : Introduction: The prevalence of chronic pancreatitis in post mortem studies is between 6–12%. We previously studied over 1800 all-comers to secondary care gastroenterology and found 14.4% had low faecal elastase-1 (FEL-1) suggestive of exocrine pancreatic insufficiency (EPI). We sought to investigate if there were similar rates in primary care. Method: A retrospective analysis of primary care patients tested for EPI between 2009–13 was performed. FEL-1 <200 was considered abnormal. Demographics, indication, co-morbidities and response to Creon were noted. Patients were excluded if the test originated in secondary care. Pancreatic imaging results were noted. Logistic regression helped determine if co morbidity or symptom could predict EPI. Comparisons were made with the secondary care cohort. Results: 168 primary care patients and 1887 ssecondary care patients were identified. The mean age in primary care was 59.74 (SD 16.26, 98 female) cf secondary care mean age 51.60 (SD 16.91, 1144 female) p < 0.0001. The most frequent indications to test in primary care were diarrhoea (60.1% 101/168), weight loss (14.9% 25/168) and abdominal pain (13.1% 22/168). In secondary care the most common indications were diarrhoea (68.4% 1252/1887), abdominal pain (20.0% 378/1887) and weight loss (6.6% 125/1887). The overall prevalence of EPI in primary care was 20.2% (FEL-1 <200) and 11.9% (FEL <100). In secondary care the overall prevalence of EPI was 14.4% (FEL-1 <200) and 8.6% (FEL-1 <100). In primary care patients with weight loss, abdominal pain and diarrhoea the rates of FEL-1 <200 were 28.0% (7/25), 18.2% (4/22) and 16.8% (17/101) respectively. 79.4% (27/34) of primary care patients with FEL-1 <200 had abdominal imaging (CT/MRI/USS); pancreatic pathology was detected in 59.6% (16/27). 86.8% of secondary care patients with FEL-1 <200 had imaging; 38.1% (90/236) had pathology (p = 0.04). Weight loss and steatorrhoea were significantly associated with FEL-1 <200 using binary logistic regression (p < 0.05). Diabetes mellitus, coeliac disease and excess alcohol consumption were strongly associated with pancreatic insufficiency (p < 0.05). 76.5% (26/34) patients had documented pancreatic enzyme supplementation, of which 80.7% (21/26) reported symptomatic relief. 7.7% reported no benefit and 11.5% were unable to tell. Conclusion: This is the first primary care study reporting a prevalence of exocrine pancreatic insufficiency (20.2%). Primary care physicians are correctly identifying patients for testing presenting with weight loss and steatorrhoea, as well as considering the associations of diabetes, coeliac disease and excess alcohol. Imaging and symptomatic benefit (from Creon) supports their diagnosis in almost 60% and 80% respectively. Disclosure of interest: None Declared.